Pengaruh Kepemimpinan Transformasional TerhadapKinerja Karyawan Pada PerusahaanBatik Brotoseno Sragen - Azizah, Rini Nur, Lukman Hakim, S.E.,M.Si (2016)
Interest in the study are: (1) To analyze the effect of transformational leadership consists of the ability to empathize, actions that reflect the mission, self-esteem, behavioral development of self-image, confidence in the competence of subordinates, behavioral creation of opportunities for followers to experience success have an influence on performance employees at the company Batik Brotoseno Sragen? (2) to analyze which variables are the most dominant influence on the performance of employees at the company Batik Brotoseno Sragen? This research is quantitative. The sample used in this study were as many as 30 respondents using purposive technique sampling.Metode data analysis using: (1) test the research instrument, namely the validity and reliability, (2) test the classic assumption, namely multicollinearity test, normality test and test heteroskedastisitas (3) testing multiple linear regression (4) test the hypothesis, that the t test, F test and coefficient of determination. The results of data analysis showed that: (1) Test instruments, all questionnaires declared valid and reliable. (2) Test the classical assumption, there is no error in the classical assumption, (3) The results of hypothesis testing, the results obtained: (a) The results of the t test showed that the variables Displays Empathy and assures followers of Their Competency individually no positive significant effect on employee performance this is indicated by the significance value greater than 0.05, while the variable Dramatizes the Misssion, Projects Self Assurances, enhances the Leader's Image and followers Provides Opportunities to Experience Success with individually has a significant positive effect on employee performance. (B) F test results showed that all variables are jointly significant effect on the performance of employees, this is indicated by the significance value less than 0.05. (C) The results of multiple linear regression test showed that the regression coefficient variable with followers Provides Opportunities to Experience Success has a regression coefficient value most, so that variables with followers Provides Opportunities to Experience Success is the most dominant variable affecting employee performance compared with other variables. (D) The results obtained figures coefficient determination coefficient R Square of 0.866 or 86.6%, meaning that the variable transformational leadership is able to explain the variation of the variable performance of employees at the company Batik BrotosenoSragen of 86.6% and the remaining 13.4% is influenced by other variables outside the model.